(untitled) (Research, Society and Development, 2021)
The WHO (World Health Organization) classifies anxiety as: generalized anxiety disorder, panic disorder, social or specific phobias and social anxiety disorder (SAD). All types share common symptoms, including feelings of malaise, panic and fear, sleep problems, not being able to stay calm, being cold and/or sweating, shortness of breath, heart palpitations, dry mouth, nausea, and prevention of situations, these disorders end up harming the quality of life of many people and often leading to suicide. The aim of the present study was to describe the effectiveness of using cannabidiol for the treatment of anxiety, to describe the physiological mechanisms and its adverse effects. For this, a literature search was carried out through published and current articles where it was possible to analyze its effects on animals and humans, the studies were carried out in a population aged 18-37 years with social anxiety disorder, public speaking phobia and people with post-traumatic disorder caused by childhood trauma. The results showed that cannabidiol can be a powerful option for the treatment of anxiety, its effectiveness in relation to dosage, administration routes and adverse effects showed significant results. The present study demonstrates that more clinical and placebo-controlled studies are needed to demonstrate the effectiveness of cannabis.